Cultural Education of Children of Indonesian Workers in Sabah, Malaysia - Haryati, Titik; Adhi Suciptaningsih, Oktaviani; Adhi Sucipta, Novianto (KnE Social Sciences, 2024)
Education and culture are related to each other and support each other in creating cultural identity in students. This research aims to analyze the cultural education of children of Indonesian workers in Sabah, Malaysia. The research method uses qualitative case studies. Five teachers, 25 students, two school principals, 25 parents, and one employee of the Consulate General of the Republic of Indonesia in Kinabalu were interviewed in depth to obtain valid data. Apart from that data collection was carried out by observing the cultural education of the workers’ children and conducting document studies. Data analysis was done using the Stake stage. The research results show that education is an effective way to transfer cultural values to students because, in education, the transfer of cultural values is carried out in a systematic, structured, and measurable way. Cultural education for the children of Indonesian workers in Sabah, Malaysia is carried out in families, schools, and the community. Families, schools, and communities must work together to transfer Indonesian cultural values. Cultural education can help create Indonesian culture in the people even though they were not born, did not grow and develop, did not live, and do not remain in Indonesia. Cultural education shapes the behavior of students who can socialize in their community and adapt to their environment to attain their survival. Keywords: education, culture, children of Indonesian workers